Evaluating the Cost and Utility of Mandating Schools to Stock Epinephrine Auto-injectors. (3rd September 2017) - Steffens, Chelsea; Clement, Benjamin; Fales, William; Chehade, Ahel El Haj; Putman, Kevin; Swor, Robert
Abstract: Background : The Michigan Legislature mandated that all public schools stock epinephrine auto-injectors (EAIs). A minimal amount is known regarding the incremental value of EAIs in schools. Our primary objective was to describe the frequency of administration of epinephrine for EMS patients with acute allergic reactions in public schools. Our secondary objective was to estimate the cost of mandating public schools to stock EAIs.Methods : We performed a retrospective cohort study of EMS cases with an impression of allergic reaction and who received epinephrine recorded in the 2014 Michigan EMS Information System (MI-EMSIS). We abstracted patient demographics, incident location by address to identify public schools, source of epinephrine given, and suspected allergen if known. We calculated advanced life support (ALS) response times to assess temporal impact of school EAIs in communities with ALS systems. We estimated the unsubsidized annual procurement cost of this mandate for Michigan public schools ( N = 4, 039), using range of costs for the required 2 EAIs (adult and pediatric) as estimated by the legislature ($140/each) and recently reported costs for commercial sources ($1, 200). Training costs were not included. Descriptive statistics are reported.Results : During this period, there were 1, 550, 009 EMS cases in the state with 631 receiving non-cardiac arrest epinephrine for presumed anaphylaxis, of which 23 cases were in public schools. Reported allergens were most often food 12 (51.2%), insect stings 4(22.2%) or unknown 7(30.4%). Among these patients, the source for epinephrine used was from the student, 7 (30.4%), EMS 7 (30.4%), school 7(30.4%), and unknown 2(8.7%). A majority (21, 91.3%) of the public school cases occurred in communities with ALS systems and ALS response was relatively rapid (median response 6 minutes, 90 percentile, 13 minutes). The unsubsidized annual cost of Michigan public schools to stock EAIs ranges from $565, 460 to $4, 846, 800.Conclusion : In this study, few public school patients received epinephrine for anaphylaxis and the vast majority occurred in communities with rapid ALS response. The direct annual supply cost of the school EAI mandate is substantial.